Enoxaparin as bridging anticoagulant treatment in cardiac surgery. Issue 2 (4th May 2007) - Rivas-Gándara, N; Ferreira-González, I; Tornos, P; Torrents, A; Permanyer-Miralda, G; Nicolau, I; Arellano-Rodrigo, E; Vallejo, N; Igual, A; Soler-Soler, J
Abstract : Objective: To assess enoxaparin as bridging anticoagulant treatment in cardiac surgery. Methods: Prospective registry of those patients who underwent cardiac surgery in our centre between December 2003 and June 2004 and required long-term anticoagulation. Subcutaneous enoxaparin was used as bridging anticoagulant treatment according to a pre-established protocol. The global thromboembolic risk was carefully assessed in all patients. All patients were followed up for 3 months. Results: Of 140 patients who were included (mean (SD) age 66 (11); 49% female), 51 were already receiving long-term acenocumarol treatment before the index intervention. 50% of the patients were at high or very high risk for thromboembolic events in the postoperative period. The mean (SD) number of days between surgery and the first dose of anticoagulant was 2.01 (7) for acenocumarol and 1 (1.01) for enoxaparin. The mean (SD) daily dose of enoxaparin was 1.1 (0.27) mg/kg. Six thromboembolic events (4.3%; 95% CI 1.6 to 9.1) occurred, but only four of them were plausibly related to enoxaparin (2.9%; 95% CI 0.8 to 7.1). Six major haemorrhagic events (4.3%; 95% CI 1.6 to 9.1) occurred, but only three were plausibly related to enoxaparin (2.1%; 95% CI 0.4 to 6.1). Conclusions: These findings show a reasonable rate of adverse events using enoxaparin as bridging anticoagulant treatment in cardiac surgery. Randomised studies are necessary to evaluate the real efficacy and safety of enoxaparin as bridging anticoagulant treatment in cardiac surgery.